KOMPETENSI PEDOGOGIK GURU DALAM PEMBELAJARAN FIQH DI MAN KOTA BATU - Tania Sumira; Rosichin Mansur; Kukuh Santoso (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
Teacher competence in Indonesia must be considered. Often teachers of Islamicreligious education are considered monotonous in learning.In this study, teachers in learning fiqh in Man City Batu were able to process learning well. The pedagogic competence in learning fiqh in Man Batu is interesting to study. Therefore, the researchers tried to discuss: How the pedagogic competence of teachers in mastering the characteristics, communicating, and mastering evaluation and student learning outcomes in learning. This study uses qualitative research, fenomenologhy research, instruments in the form of interviews, observations, and documentation. Data collection techniques ranging from analysis to conclusion. The results fenomenologhy, the teacher's pedagogic competence can master the differences in student characteristics, can understand students based on their initial behavior, teachers can deal with the causes of student deviations, pedagogical competence of teachers in communicating effectively with students and among students, teachersare able to listen to student questions, teacher competence in evaluating learning in the form of cognitive, affective, and psychomotor abilities.